The regional impact of neo-liberal policies in Brazil - Baer, Werner; Haddad, Eduardo; Hewings, Geoffrey (Economia Aplicada, 1998)
This article focuses on the regional dimension of the traditional dilemma of “equity vs. efficiency” as exemplified by the case of Brazil. The main question addressed is whether a more market-oriented and open economy leads to an increased or decreased concentration of income, and whether there is a natural regional “trickle down” effect when unfettered market forces increase regional concentration of economic growth. In the first part of the article these questions are examined from an historical perspective, while the second part concentrates on the regional impact of the open market policies of 1990s.